2020
DOI: 10.1158/1078-0432.ccr-20-0268
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic Targeting of CUB Domain Containing Protein 1 (CDCP1) in Pancreatic Cancer

Abstract: Purpose: The recent emergence of radioligand therapies for cancer treatment has increased enthusiasm for developing new theranostic strategies coupling both imaging and cytotoxicity in the same entity. In this study, we evaluated whether CUB domain containing protein 1 (CDCP1), a single-pass transmembrane protein highly overexpressed in diverse human cancers, might be a target for cancer theranostics.Experimental Design: The ectodomain of CDCP1 was targeted using radiolabeled forms of 4A06, a potent and specif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…[17] Importantly, subsequent investigations established CD318 as a viable target for radiological staging and treatment of pancreatic cancer. [47,64] In this study, we confirmed exclusive expression of CD146, CD99 and CD239 on the surface of 3D-grown NCI-H23 cells ( Figure 4B) and showed their potential interaction through the activation of protein networks facilitated by PI3K, NFkB, and IFN-beta signaling ( Figure 4A). A recent study focused on the evaluation of the KRas G12C direct covalent inhibitor ARS1620 using patient-derived xenograft (PDX) models and found that intrinsic resistance of NSCLC to ARS1620 monotherapy, driven by nongenetic adaptive mechanisms, can be alleviated by concomitant application of PI3K inhibitors.…”
Section: Discussionsupporting
confidence: 66%
“…[17] Importantly, subsequent investigations established CD318 as a viable target for radiological staging and treatment of pancreatic cancer. [47,64] In this study, we confirmed exclusive expression of CD146, CD99 and CD239 on the surface of 3D-grown NCI-H23 cells ( Figure 4B) and showed their potential interaction through the activation of protein networks facilitated by PI3K, NFkB, and IFN-beta signaling ( Figure 4A). A recent study focused on the evaluation of the KRas G12C direct covalent inhibitor ARS1620 using patient-derived xenograft (PDX) models and found that intrinsic resistance of NSCLC to ARS1620 monotherapy, driven by nongenetic adaptive mechanisms, can be alleviated by concomitant application of PI3K inhibitors.…”
Section: Discussionsupporting
confidence: 66%
“…and Dammes & Peer for further detail [ 206 , 207 ]. Antibody-based theranostic pairs have been developed targeting a variety of antigens including carcinoembrionic antigen (CEA) [ 208 ], tissue factor [ 35 ], CUB domain containing protein 1 (CDCP1) [ 209 ] and Met [ 210 ]. For instance, Knutson and colleagues have reported the development of a theranostic monoclonal antibody specific for CEA, conjugated to paclitaxel and a PEGylated near-infrared fluorophore (DyLight™ 680-4xPEG, Thermo Fisher Scientific, #46603, Rockford, IL, USA).…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…We next evaluated if CDCP1 expression can be detected on PET using 89 Zr-labeled 4A06. 4A06 was functionalized with desferrioxamine B and radiolabeled to high yield with Zr-89 as previously reported (13). A cohort of mice (n = 4/tumor type) bearing one of the following tumors were studied: TRAMP C2, DU145, 22Rv1, LTL-545 and LTL-331.…”
Section: Tumor Autonomous Expression Of Cdcp1 In Mcrpc Is Detectable With 89 Zr-4a06mentioning
confidence: 99%
“…We chose this dosing regimen as we previously showed it to be more efficacious that a single fraction of an equivalent total radioactive dose (i.e. 800 μCi) (13). SPECT/CT imaging showed effective tumor targeting at 72 hours after the first injection (Figure 4A).…”
Section: Radioligand Therapy With 177 Lu-4a06 Inhibits Mcrpc Tumor Growthmentioning
confidence: 99%
See 1 more Smart Citation